Release angles for shooting - Miller, S. (coachesinfo.com)
The relationship between ball release angle and the chances of the ball going through the hoop is complex. The main factors to be considered are the effort required to get the ball to the basket, and the margin for error that the ball has when it gets to the basket. Author points out the release angles.